Physical Activity and Other Determinants of Survival in the Oldest Adults. Issue 2 (30th November 2016) - Muscari, Antonio; Bianchi, Giampaolo; Forti, Paola; Giovagnoli, Marco; Magalotti, Donatella; Pandolfi, Paolo; Zoli, Marco; ,
Abstract : Objectives: To determine the role of physical activity as a possible survival determinant in the oldest adults. Design: Prospective, longitudinal, population‐based cohort. Setting: The Pianoro Study of community‐dwelling older adults in three towns in northern Italy. Participants: Noninstitutionalized individuals aged 85 and older (n = 500; mean age 89.6 ± 3.1, 65% female). Measurements: Participants provided information on marital status, educational level, previous work activity, cardiovascular risk factors, previous cardiovascular events, self‐rated health, joint pain, and functional status. Physical activity was quantified using the Physical Activity Scale for the Elderly. Seven‐year mortality was known for all subjects. Results: During the 7 years of follow‐up, 365 subjects died. According to Cox proportional hazards regression, the following factors were found to be independently associated with mortality: PASE score (hazard ratio (HR) = 0.987, 95% confidence interval (CI) = 0.981–0.993, P < .001), male sex (HR = 1.642, 95% CI = 1.411–2.068, P < .001), age in years (HR = 1.077, 95% CI = 1.040–1.116, P < .001), previous stroke (HR = 1.908, 95% CI = 1.362–2.673, P < .001), poor self care (HR = 1.662, 95% CI = 1.231–2.246, P < .001), neck pain (HR = 0.649, 95% CI = 0.497–0.849, P = .002), self rated health (HR = 0.991, 95% CI = 0.985–0.997, P = .002). Conclusion: In the oldest adults, accurate quantification of physical activity may provide important prognostic information. The predictive value of cardiovascular risk factors, except age, male sex, and prior stroke, was confirmed to be negligible. An unexpected inverse association between neck pain and mortality may require further investigation.